Emergency right liver lobectomy - Torterolo, Edgardo; Castiglioni, Juan C; Bergalli, Luis; Cuneo, Roberto; Terra, José G; Muchada, Raúl (Cirugía del Uruguay, 1973)
Description of right hepatic lobectomy due to serious open traumatism of liver. The paper analyzes its evolution.